Madly Madagascar - Twentieth Century Fox Home Entertainment, Inc. ([Beverly Hills, Calif.] : 20th Century Fox Home Entertainment, 2013)
Your favorite Madagascar pals are back in an all-new adventure! Alex's favorite holiday, Valentine's Day, brings hilarious surprises and excitement for the entire gang. Melman plans a big surprise for Gloria, Marty tries to impress a new friend and everyone wants to get their hands on King Julien's love potion. Bonus features included.
Title from disc surface.
Special features: All-new short first flight and more!
Rating: Not rated.
DVD; Dolby digital 5.1 (English), Dolby digital 2.0 surround (Spanish).
English or Spanish dialogue; Spanish or French subtitles; English SDH.
Keywords: Jungle animals -- Juvenile films; Friendship -- Juvenile films; Surprise -- Juvenile films; Madagascar -- Juvenile films; Short films; Children's films; Animated films; Films for the hearing impaired